2017
DOI: 10.1089/scd.2016.0218
|View full text |Cite
|
Sign up to set email alerts
|

Different Donors Mesenchymal Stromal Cells Secretomes Reveal Heterogeneous Profile of Relevance for Therapeutic Use

Abstract: Duchenne muscular dystrophy (DMD) is a lethal X-linked disorder caused by null mutations in the dystrophin gene. Although the primary defect is the deficiency of muscle dystrophin, secondary events, including chronic inflammation, fibrosis, and muscle regeneration failure are thought to actively contribute to disease progression. Despite several advances, there is still no effective therapy for DMD. Therefore, the potential regenerative capacities, and immune-privileged properties of mesenchymal stromal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 40 publications
1
41
0
3
Order By: Relevance
“…Whether this was due to an effect of QDs or to drift of MSC immunophenotype over the passages in separate cultures is not clear, and further studies are needed in this area. Although molecular markers continue to be used to characterize stem cell populations, recent studies with human MSCs indicate that cells isolated from different donors (Szepesi et al, ) or from different sites from the same donor (Hatakeyama et al, ; Sacchetti et al, ) and cells treated with different enzymatic digestion methods for detachment (Tsuji et al, ) can have different surface antigen expression and even MSCs with identical cell surface phenotype from different tissues and donors have distinct transcriptomic signatures and differentiation capacities, likely due to the broad overlap of cells with MSC markers with other cell populations (Assoni, Coatti, Valadares, et al, ; Sacchetti et al, ). Thus, the immunophenotypic characterization of MSCs remains unclear, and MSCs are currently best defined functionally.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this was due to an effect of QDs or to drift of MSC immunophenotype over the passages in separate cultures is not clear, and further studies are needed in this area. Although molecular markers continue to be used to characterize stem cell populations, recent studies with human MSCs indicate that cells isolated from different donors (Szepesi et al, ) or from different sites from the same donor (Hatakeyama et al, ; Sacchetti et al, ) and cells treated with different enzymatic digestion methods for detachment (Tsuji et al, ) can have different surface antigen expression and even MSCs with identical cell surface phenotype from different tissues and donors have distinct transcriptomic signatures and differentiation capacities, likely due to the broad overlap of cells with MSC markers with other cell populations (Assoni, Coatti, Valadares, et al, ; Sacchetti et al, ). Thus, the immunophenotypic characterization of MSCs remains unclear, and MSCs are currently best defined functionally.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, potency tests should also be developed to discriminate MSCs populations with the appropriate activity for a desirable anti-tumor effect. It has been observed that MSCs secrete different proteins even when they are obtained from the same tissue of different donors or from different tissues of the same donor (158). Additionally, MSCs activity is known to decline with donor's age (159).…”
Section: Resultsmentioning
confidence: 99%
“…Another study revealed that altered cell migration resulting from changes in MSC surface markers during prolonged cultivation could significantly reduce MSC homing ability (Jung et al, 2011). Though MSCs isolated from multiple sources share similar phenotypic characteristics, there have been proven differences in therapeutic potential based upon their origin (Vieira et al, 2010; Eiro et al, 2014; Assoni et al, 2017).…”
Section: Challenges Of Using Mscs In Cell Therapymentioning
confidence: 99%